Renal Resistance Trend During Hypothermic Machine Perfusion Is More Predictive of Postoperative Outcome Than Biopsy Score: Preliminary Experience in 35 Consecutive Kidney Transplantations. Issue 7 (30th March 2018) - Bissolati, Massimiliano; Gazzetta, Paolo Giovanni; Caldara, Rossana; Guarneri, Giovanni; Adamenko, Olga; Giannone, Fabio; Mazza, Michele; Maggi, Giulia; Tomanin, Deborah; Rosati, Riccardo; Secchi, Antonio; Socci, Carlo
Abstract: Hypothermic machine perfusion (HPM) grants a better postoperative outcome in transplantation of organs procured from extended criteria donors (ECDs) and donors after cardiac death (DCD). So far, the only available parameter for outcome prediction concerning those organs is pretransplant biopsy score. The aim of this study is to evaluate whether renal resistance (RR) trend during HPM may be used as a predictive marker for post‐transplantation outcome. From December 2015 to present, HMP has been systematically applied to all organs from ECDs and DCD. All grafts underwent pretransplantation biopsy evaluation using Karpinski's histological score. Only organs that reached RR value ≤1.0 within 3 hours of perfusion were transplanted. Single kidney transplantation (SKT) or double kidney transplantation (DKT) were performed according to biopsy score results. Sixty‐five HMPs were performed (58 from ECDs and 7 from DCD/ECMO donors). Fifteen kidneys were insufficiently reconditioned (RR > 1) and were therefore discarded. Forty‐nine kidneys were transplanted, divided between 21 SKT and 14 DKT. Overall primary nonfunction (PNF) and delayed graft function (DGF) rate were 2.9 and 17.1%, respectively. DGF were more common in kidneys from DCD (67 vs. 7%; P  = 0.004). Biopsy score did not correlate with PNF/DGF rate ( P  = 0.870) and postoperative creatinine trend ( P  = 0.796). Recipients of kidneys that reached RR ≤ 1.0 within 1 hour of HMP had a lower PNF/DGF rate (11 vs. 44%; P  = 0.033) and faster serum creatinine decrease (POD10 creatinine: 1.79 mg/dL vs. 4.33 mg/dL; P  = 0.019). RR trend is more predictive of post‐transplantation outcome than biopsy score. Hence, RR trend should be taken into account in the pretransplantation evaluation of the organs.